Testosterone in males with COVID‐19: A 7‐month cohort study. (31st August 2021) - Salonia, Andrea; Pontillo, Marina; Capogrosso, Paolo; Gregori, Silvia; Carenzi, Cristina; Ferrara, Anna Maria; Rowe, Isaline; Boeri, Luca; Larcher, Alessandro; Ramirez, Giuseppe A.; Tresoldi, Cristina; Locatelli, Massimo; et al.
Abstract: Background: Circulating testosterone levels have been found to be reduced in men with severe acute respiratory syndrome coronavirus 2 infection, COVID‐19, with lower levels being associated with more severe clinical outcomes. Objectives: We aimed to assess total testosterone levels and the prevalence of total testosterone still suggesting for hypogonadism at 7‐month follow‐up in a cohort of 121 men who recovered from laboratory‐confirmed COVID‐19. Materials and methods: Demographic, clinical, and hormonal values were collected for all patients. Hypogonadism was defined as total testosterone ≤9.2 nmol/L. The Charlson Comorbidity Index was used to score health‐significant comorbidities. Descriptive statistics and multivariable linear and logistic regression models tested the association between clinical and laboratory variables and total testosterone levels at follow‐up assessment. Results: Circulating total testosterone levels increased at 7‐month follow‐up compared to hospital admittance ( p < 0.0001), while luteinizing hormone and 17β‐estradiol levels significantly decreased (all p ≤ 0.02). Overall, total testosterone levels increased in 106 (87.6%) patients, but further decreased in 12 (9.9%) patients at follow‐up, where a total testosterone level suggestive for hypogonadism was still observed in 66 (55%) patients. Baseline Charlson Comorbidity Index score (OR 0.36; p = 0.03 [0.14, 0.89]) was independently associated with total testosterone levels at 7‐month follow‐up, after adjusting for age, BMI, and IL‐6 at hospital admittance. Conclusions: Although total testosterone levels increased over time after COVID‐19, more than 50% of men who recovered from the disease still had circulating testosterone levels suggestive for a condition of hypogonadism at 7‐month follow‐up. In as many as 10% of cases, testosterone levels even further decreased. Of clinical relevance, the higher the burden of comorbid conditions at presentation, the lower the probability of testosterone levels recovery over time.